The reported impact of public involvement in biobanks: a scoping review - Luna,Puerta L; Kendall,W; Davies,B; Day,S; Ward,H (Health Expectations, 2020)
BackgroundBiobanks increasingly employ public involvement and engagement strategies, though few studies have explored their impact. This review aims to (a) investigate how the impact of public involvement in biobanks is reported and conceptualized by study authors; in order to (b) suggest how the research community might reconceptualize the impact of public involvement in biobanks.MethodsA systematic literature search of three electronic databases and the INVOLVE Evidence Library in January 2019. Studies commenting on the impact of public involvement in a biobank were included, and a narrative review was conducted.Results and discussionFortyone studies covering thirtyone biobanks were included, with varying degrees of public involvement. Impact was categorized according to where it was seen: ‘the biobank’, ‘people involved’ and ‘the wider research community’. Most studies reported involvement in a ‘functional’ way, in relation to improved rates of participation in the biobank. Broader forms of impact were reported but were vaguely defined and measured. This review highlights a lack of clarity of purpose and varied researcher conceptualizations of involvement. We pose three areas for further research and consideration by biobank researchers and public involvement practitioners.ConclusionsFunctional approaches to public involvement in biobanking limit impact. This conceptualization of involvement emerges from an entrenched technical understanding that ignores its political nature, complicated by longstanding disagreement about the values of public involvement. This study urges a reimagination of impact, reconceptualized as a twoway learning process. More support will help researchers and members of the public to undergo such reflective exercises.